Reliability of shape memory effect based polymeric temperature sticker for cold chain logistic - Koh, Fu Kai (2016)
The shape memory polymers (SMPs) exist in numerous categories and classes. The most widely used shape-memory materials are acknowledged as shape-memory alloys (SMAs) that retain shape memory effect due to stable crystalline materials. However, SMAs have some limitations in applicability such as high stiffness, high cost, inflexible transition temperature, and so forth. Alternatively, materials such as shape memory polymers have been developed to overcome the limitations. The mechanisms for shape-memory effects of polymeric materials differ from metal alloys. In fact, the shape memory polymers can be termed as stimuli-sensitive materials because of their capability of responding to certain changes in their environment. Moreover, stimuli-responsive shape-changing polymers can be classified as one-way shape memory polymers (OWSMPs), two-way shape-changing polymers (TWSCPs) and stimuli-responsive hydrogels. Shape memory polymers consist of netpoints which are either physically or chemically cross-linked structures. The netpoints crosslink the chain segments and becomes the determining factor of the permanent shape. SMPs achieve temporary strain fixing and recovery results in large extensibility that comes from the intrinsic elasticity of their polymeric networks. The efficiency of SMPs to remember the respective permanent shape also depend on age. Moreover, SMPs have broad applications including aerospace, sensors, textiles, household products, actuators, data storage media and so forth but their applicability in biomedical is remarkable. In this report, various materials such as Thermoplastic Polyurethane (TPU265A), Low Melting Point Wax ( LMPW), High Melting Point Wax were tested for their stability through differential scanning calorimetric (DSC) test furthermore, tensile test were carried out and the shape recovery of the materials were elevated using different temperatures .